2017
DOI: 10.1080/14767058.2017.1344632
|View full text |Cite
|
Sign up to set email alerts
|

A model to predict risk of postpartum infection after Caesarean delivery*

Abstract: Purpose: The purpose of this study is to build and validate a statistical model to predict infection after caesarean delivery (CD). Methods: Patient and surgical variables within 30 d of CD were collected on 2419 women. Postpartum infection included surgical site infection, urinary tract infection, endomyometritis and pneumonia. The data were split into model development and internal validation (1 January-31 August; N ¼ 1641) and temporal validation subsets (1 September-31 December; N ¼ 778). Logistic regressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 39 publications
0
7
0
2
Order By: Relevance
“…Asthma had a significantly increased risk of postoperative complications, which were superficial surgical site infections. History of asthma has been established as a risk factor for perioperative respiratory adverse events, 6 and multiple studies have demonstrated that history of asthma can be significantly associated with surgical site infections, [7][8][9] although causation remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Asthma had a significantly increased risk of postoperative complications, which were superficial surgical site infections. History of asthma has been established as a risk factor for perioperative respiratory adverse events, 6 and multiple studies have demonstrated that history of asthma can be significantly associated with surgical site infections, [7][8][9] although causation remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…17 There is interest in developing more complicated modeling for the prediction of infection following CD. 18 While the overall rate of infection in the setting of IUPC is low, there is a potential for its incorporation into more complex modeling to identify patients who would benefit from postoperative prophylaxis.…”
Section: Discussionmentioning
confidence: 99%
“…Имеются противоречивые сведения о влиянии назначения более высоких доз антибиотиков на инфекционные исходы, в связи с чем эта модель также может быть полезна в данной ситуации -с расчетом конкретного индивидуального риска с учетом нескольких факторов [2,7,13,22,24,38]. При повышении порога рассматривается возможность назначения дополнительной терапии или более тщательное наблюдение в послеоперационном периоде, что в случае порога принятия решения с риском от 5 до 55% должно быть более целесообразно и эффективно по сравнению с лечением или мониторингом всех пациенток с высоким риском без увеличения ложноположительных результатов.…”
Section: интерпретация результатов исследованияunclassified
“…Современные исследования подтверждают, что комплексные пред-, пери-и профилактические послеоперационные мероприятия, могут привести к снижению акушерской инфекции [1,5,10,[17][18][19][20][21]. Существуют определенные группы пациенток, подвергающихся значительно более высокому риску развития инфекционных осложнений, поэтому их выявление с реализацией мер по инфекционному контролю, по мнению большинства клиницистов, является наиболее рациональным [6,8,[22][23][24][25]. Эффективность профилактических мероприятий при воспалительных осложнениях пуэрперия значительно возрастает при их ранней диагностике или прогнозировании вероятности с учетом соответствующих факторов риска.…”
Section: Introductionunclassified